2010
DOI: 10.1016/j.ejvs.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Treatment for Venous Aneurysm Complicating Vascular Access Arteriovenous Fistula: Use of an Exoprosthesis to Reinforce the Vein after Aneurysmorrhaphy

Abstract: Reinforced venous aneurysmorrhaphy is effective in controlling venous dilation and achieving patency. Reduction of high-flow rates was not always achieved. Further study is needed to evaluate long-term efficacy of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 15 publications
(14 reference statements)
4
49
0
2
Order By: Relevance
“…This technique was developed by our group in 2008 9 and has been validated 10 and internationally adopted for aneurysmal AVF salvage. 11 A detailed video of this procedure can be found online (http://aneurysmorrhaphy.eu-How to use section). In brief, the aneurysmal fistula was mobilized, and general heparinization (5000-10 000 IU) was performed.…”
Section: Avf Reductionmentioning
confidence: 99%
“…This technique was developed by our group in 2008 9 and has been validated 10 and internationally adopted for aneurysmal AVF salvage. 11 A detailed video of this procedure can be found online (http://aneurysmorrhaphy.eu-How to use section). In brief, the aneurysmal fistula was mobilized, and general heparinization (5000-10 000 IU) was performed.…”
Section: Avf Reductionmentioning
confidence: 99%
“…The cause of the dilatation was degenerative mechanisms in the vein wall that resulted from repeated cannulation during dialysis, the increased blood pressure in the arterialized vein and the repeated angioplasty for the treatment of recurrent stenosis [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Berard et al noted that reinforced venous aneurysmorrhaphy is effective in controlling venous dilation and achieving patency 11. Also, Balaz et al found that to offset the weakening of the venous wall by suture following aneurysmorrhaphy, an external polyethylene terephthalate prosthesis needed to be implanted in the vein to prevent the development of intimal hyperplasia in the de novo created AV fistula 12.…”
Section: Discussionmentioning
confidence: 99%